Are Oxinium Femoral Heads Superior to Alternative Bearing Surface Materials? A Systematic Review - Zou, Anthony H.; Feng, James E.; Novikov, David; O'Connor, Casey M.; Anoushiravani, Afshin A.; Schwarzkopf, Ran; Vigdorchik, Jonathan M. (The Journal of Hip Surgery, 2020)
Oxidized zirconium (OxZr) femoral heads were developed to emulate the superior wear and scratch properties of ceramics while eliminating their unwanted tendency for brittle fracturing. Studies using OxZr have demonstrated reduced linear and volumetric wear of polyethylene (PE) liners when compared with cobalt chrome, ceramic, and steel femoral heads. The purpose of this systematic review was to determine the difference in revision rates, radiologically determined linear wear rates, and patient-reported outcomes among OxZr and alternative bearing materials. Following the Preferred Reporting Items for Systematic Review and Meta-Analysis protocols, a systematic review of published literature through April 24, 2018 was conducted. Among the 862 cases included at a mean weighted follow-up of 4.78 years, the revision THA rate and patient-reported outcomes were similar among OxZr and alternative bearing materials. One of the five studies demonstrated significantly lower linear wear rates in the OxZr group when paired with ultrahigh molecular-weight PE (OxZr 0.03 mm/y vs. stainless-steel 0.11 mm/y; p < 0.001) and when paired with highly-crosslinked PE (OxZr 0.02 mm/y vs. stainless-steel 0.04 mm/y; p < 0.001). The remaining four studies found no difference in linear wear rates. OxZr demonstrated similar outcome to that of modern-day ceramic and metal femoral heads for short- and mid-term revision surgery rates and patient-reported outcomes. Longer term studies are needed to evaluate if any long-term wear advantages are seen with the use of OxZr femoral heads and if the use of OxZr is cost effective compared with ceramic or metal alternatives. The level of evidence of the study is level II, systematic review.
Keywords: total hip arthroplasty; bearing surface materials; oxidized zirconium